Web personalization research: an information systems perspective - Krishnaraju, Vinodh; Mathew, Saji K (Journal of systems and information technology, 2013)
Purpose - Web personalization has been studied in different streams of research such as Marketing, Human Computer Interaction and Computer Science. However, an information systems perspective of web personalization research is very scarcely visible in this body of knowledge. This research review seeks to address two important questions: how has web personalization evolved as an integrative discipline? How has web personalization been treated in IS literature and where should researchers focus next?Design methodology approach - The paper intently follows an information systems perspective in its thematic classification of web personalization research which is consistent with the early conceptualization of information systems by logically mapping IS categories into web personalization research streams. Articles from 100+ journals were analyzed and important concepts related to web personalization were classified from an information systems perspective.Findings - Surrounding the theme of web personalization two parallel streams of research evolved. First stream consisted of internet business models, computer science algorithms and web mining. Second stream focussed on human computer Interaction studies, user modelling and targeted marketing. Future information systems researchers in web personalization must focus on four important areas of social media, web development methodologies, emerging Internet accessing gadgets and domains other than e-Commerce.Originality value - Web personalization has been studied previously in separate research streams. But no integrated view from different research streams exists. Although research interest in web mining has been growing as evidenced by growing number of publications an information systems perspective of web personalization research is very scarcely visible in the body of knowledge. The authors intently follow an information systems perspective in their thematic classification of web personalization research which is consistent with the early conceptualization of information systems by logically mapping IS categories into web personalization research streams. This thematic segregation of different research streams into IS framework makes our study distinct from other early reviews. They also identify four important areas where future IS researchers should focus on.